Managerial style and its managerial implications for organizations in the Slovak republic - Vargic, Branislav; Luptakova, Stanislava (Journal of Business Economics and Management, 2003)
The article presents outcomes of a survey focusing on a style of management in Slovak organizations, using Blake & Mouton's managerial grid. The results presented ate based on a survey, consisting of a sample of 512 questionnaires addressing all managerial levels in Slovak companies. The corporations included in the survey are from various industries and fields of business as well as of different financial and capital ownership structures. The main objective of the survey is to portray management style of the managers in Slovakia from the perspective of managerial grid, analyzing people or task orientation in their managerial work. Further, the paper illustrates the differences in management style regarding the gender and the capital ownership of the company and depicts the consistency of the management style in relation to subordinates with the preferred management style from the superiors.First Published Online: 14 Oct 2010